2001
DOI: 10.2466/pms.2001.93.2.387
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Internal Speed Control and Psychophysiological Response during Continuous Forearm Rotation Movement

Abstract: This study investigated the properties of speed control and psychophysiological response when subjects changed movement speed internally. The task consisted of a continuous forearm rotational movement, which 14 women performed under 3 conditions, namely, (1) Preferred: the subject performed the task at a freely selected speed, (2) Slow: the subject changed the speed in two steps from preferred to a slower pace (slow, then very slow), (3) Fast: the subject changed the speed in two steps from preferred to a fast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It could be that slow movements with high gain are difficult because of the slowness of the hand movements; participants may have preferred to move faster. Studies have shown that there is a preferred movement speed for continuous movements, which also influences how movements at other speeds are performed (Naruse et al, 2001). This interpretation is corroborated by the results on the CE, which indicated that participants were more in lead of the stimulus with higher gains and slower speed.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that slow movements with high gain are difficult because of the slowness of the hand movements; participants may have preferred to move faster. Studies have shown that there is a preferred movement speed for continuous movements, which also influences how movements at other speeds are performed (Naruse et al, 2001). This interpretation is corroborated by the results on the CE, which indicated that participants were more in lead of the stimulus with higher gains and slower speed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the PP can be seen as a psychological standard for the judgement of a set of actions in the overall movement perception (Tajima & Choshi, 1999). Movements at a speed close to the PP are perceived as syntonic movements and those about 30-40% slower or faster than the PP are seen as non-syntonic movements (Naruse, Sakuma, & Hirai, 2001). This syntony between the presented video speed and person's sense of movement speed may have influenced the player's predictive skill and visual search activities.…”
Section: Discussionmentioning
confidence: 99%
“…During the exercises, each subject alternated between the right and left limbs for abduction, adduction, and hip flexion. The subjects gradually increased the exercise speed every 10 s, from the slowest to the fastest possible speed, according to their perceptions [ 30 ]. Each volunteer performed random movements with the calibration wand that were recorded for 50 s (equating to 5000 frames) within the carefully defined zone corresponding to the collective field of view of all cameras, as illustrated in Figure 2 a.…”
Section: Methodsmentioning
confidence: 99%